Plant Life - Smith, Dwight G.; Avery, David F.; Schultz, Marcia H. (Southern Connecticut State University ; Pearson Custom Pub., 2000)
Keywords: Nomenclature; Plants; Plants; dept.egm; faculty_collection

Three new species of Jaltomata (Solanaceae) from Ancash, Peru - Mione, T.; Leiva G., S.; Yacher, L. (Novon, 2000)
Three new Jaltomata species from the department of Ancash, Peru, are described and illustrated. The three species are distinguished from others in the genus by features of the flowers, hairs, and leaves. Fruits of Jaltomata cajacayensis S. Leiva and Mione are gathered for consumption. Jaltomata lomana Mione and S. Leiva is known only from a single fog-dependent plant community, a lomas formation. Jaltomata yungayensis Mione and S. Leiva is widely distributed at high elevations.
Keywords: Jaltomata; Jaltomata cajacayensis; Jaltomata lomana; Jaltomata yungayensis; Magnoliophyta; Solanaceae; dept.egm

Lessons in managed destination competitiveness: the case of Foxwoods casino resort. - d'Hauteserre, Anne-Marie (Tourism Management, 2000)
Foxwoods, which started as a Binge gaming facility, has become the largest casino in the western world. It is one of the most competitive tourist destinations in the world and can teach a few lessons about managing competitiveness. The visionary entrepreneurial activity, strategic management decisions of its owners and the Mashantucket Pequots are the reasons for its existence and its success, not some circumstantial fluke. The Pequots understood the destination's potential initial advantage. They then sought to avoid that Foxwoods casino and resort slip into McGambling or wither in the face of increasing competition for the entertainment/leisure dollar in the eastern United States by modifying its market positioning. They are now nudging it toward a broadly diversified base of entertainment. All along they empowered their employees to support their clear mission for the resort. Part of their strategy is to transform southeastern Connecticut into a synergistic tourist destination for their and the region's benefit. (C) 1999 Elsevier Science Ltd. All rights reserved.
Keywords: Competitiveness; Connecticut; Foxwoods; Gam(bl)ing; Strategic planning; Tourist destination; United States; competitiveness; dept.egm; gambling; management practice; recreational activity; tourism economics